The Potency of Pluchea indica Less as Preventive Effort to Lead (Pb) Pertubation on Rats (Rattus norvegicus) Organs - Aulanni'am, Aulanni'am; Julianto, Andri; Dewi, Made Artari; Dirgahariyawan, Tri Cahyo; Mahdi, Chanif; Wuragil, Dyah Kinasih; Herawati, Herawati (Veterinary Biomedical and Clinical Journal, 2019)
Lead (Pb) is one of the heavy m metals polluting the environment which is harmful to t the organism. Pb accumulation triggers free radic cals and disrupts the body's metabolism. Pluche indic ca leaf extract is reported contain flavonoids whiich act as antioxidants and can counteract free radiccal attacks. The purpose of this study was to de etermine the role of Pluchea indica leaf extract preve entive therapy in counteracting free radicals due too exposure to Pb in rats (Rattus norvegicus). Wistar mmale rats aged of 8-10 weeks with a body weight of about 200-250 grams. Rats were divided into 5 tr reatment groups, were group A as negative contr rol, group B as positive control induced by lead (Pb)) 10 mg/rat/day, groups C,D,E given with ethano olic extract of Pluche indica leavesof 200 mg/kgBW, , 400 mg/kgBW, and 600 mg/kgBW and lead (Pb b) exposure of 10mg/ rat/day. Kidney, liver and jejunaal histopathology using HE staining was observed microscopically. The results showed that the administtration of Pluche indica leaves extract could preve ent tissue damage to the kidney, liver and jejunum in rats exposured to Pb. Dose of 600 mg/kgBW show wed histopathological improvement in kidney, liver annd jejunum. The greater the dose, the better prev ention of tissue damage as indicated by tissue condition resembling those of control rats. The conclusion of this study, the Pluchea indica leaf extract has the potential to prevent organ damaged exposed to lead.